2002
DOI: 10.1038/nn842
|View full text |Cite
|
Sign up to set email alerts
|

Immunization reverses memory deficits without reducing brain Aβ burden in Alzheimer's disease model

Abstract: We have previously shown that chronic treatment with the monoclonal antibody m266, which is specific for amyloid beta-peptide (Abeta), increases plasma concentrations of Abeta and reduces Abeta burden in the PDAPP transgenic mouse model of Alzheimer's disease (AD). We now report that administration of m266 to PDAPP mice can rapidly reverse memory deficits in both an object recognition task and a holeboard learning and memory task, but without altering brain Abeta burden. We also found that an Abeta/antibody co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

48
581
5
4

Year Published

2004
2004
2015
2015

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 838 publications
(638 citation statements)
references
References 23 publications
48
581
5
4
Order By: Relevance
“…Finally, in some transgenic mice, vaccination with Ab has prevented the age dependent memory loss characteristic of such animals while only modestly decreasing the amyloid plaque burden, suggesting that the antibodies produced following the vaccination could specifically target the oligomeric species responsible for memory loss [79]. Even more remarkably, a single administration of a monoclonal antibody to Ab has recently been shown rapidly (within hours) to reverse memory impairment in certain learning and memory tasks in transgenic mouse models of Alzheimer's disease without any detectable alteration in the Ab burden, suggesting that this antibody also targets soluble Ab species that are particularly toxic [80].…”
Section: Elucidation Of the Mechanism Of Toxicitymentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, in some transgenic mice, vaccination with Ab has prevented the age dependent memory loss characteristic of such animals while only modestly decreasing the amyloid plaque burden, suggesting that the antibodies produced following the vaccination could specifically target the oligomeric species responsible for memory loss [79]. Even more remarkably, a single administration of a monoclonal antibody to Ab has recently been shown rapidly (within hours) to reverse memory impairment in certain learning and memory tasks in transgenic mouse models of Alzheimer's disease without any detectable alteration in the Ab burden, suggesting that this antibody also targets soluble Ab species that are particularly toxic [80].…”
Section: Elucidation Of the Mechanism Of Toxicitymentioning
confidence: 99%
“…Recent studies report the success of both active and passive vaccination approaches to slowing and/or reversing the aggregation process, and its pathological consequences, in mouse models of light chain amyloidosis [71], Alzheimer's disease [77,79,80,[86][87][88][89][90] and mammalian prion diseases [76,[91][92][93]. The molecular mechanisms by which antibodies act in a therapeutic manner are just beginning to be understood (for recent reviews see [94][95][96][97][98][99]) (Textbox 3).…”
Section: Therapeutic Reagentsmentioning
confidence: 99%
“…These results were interpreted to imply that insoluble Aβ is a surrogate marker for "small assemblies" of Aβ that disrupt cognition and occur as intermediates during the formation of insoluble Aβ. This finding was extended to the PDAPP strain of mice by Dodart and colleagues [50]. This group previously reported that chronic treatment of PDAPP mice with the m266 anti-Aβ antibody (every 2 weeks from 4 to 9 months of age) reduced Aβ burden at least in part by increasing peripheral clearance [55].…”
Section: Potential Uses Of An Aβ Imaging Agentmentioning
confidence: 82%
“…This group previously reported that chronic treatment of PDAPP mice with the m266 anti-Aβ antibody (every 2 weeks from 4 to 9 months of age) reduced Aβ burden at least in part by increasing peripheral clearance [55]. In the subsequent study in 24 month-old PDAPP mice [50], they found that a "subchronic" six-week course of m266 immunotherapy reversed the cognitive deficits measured, but did not decrease the Aβ immunohistochemical burden (brain Aβ levels were not determined by ELISA). More surprisingly, they found that the cognitive deficits measured in 11 month-old PDAPP mice could be reversed within days of a single dose of the m266 anti-Aβ antibody.…”
Section: Potential Uses Of An Aβ Imaging Agentmentioning
confidence: 92%
See 1 more Smart Citation